Double dissociation of function within the hippocampus: spatial memory and hyponeophagia. - Bannerman, D; Deacon, R; Offen, S; Friswell, J; Grubb, M; Rawlins, J (2002)
Complete and dorsal hippocampal lesions impaired spatial performance on 2 working memory tasks: rewarded alternation on the T maze and matching to position in the water maze. In contrast, ventral hippocampal lesions had no effect on these tasks, even when task difficulty was increased by the introduction of delays. Ventral lesions did resemble complete lesions in reducing anxiety in 3 commonly used tests of anxiety (social interaction, plus-maze, and hyponeophagia). Dorsal lesions also appeared to be anxiolytic in the social interaction and plus-maze tests, but they did not affect hyponeophagia. Complete- and dorsal-lesioned rats displayed hyperactivity, whereas ventral-lesioned rats did not. These results show a double dissociation between dorsal and ventral hippocampal lesions (hyponeophagia vs. spatial memory), suggesting differentiation of function along the septotemporal axis of this structure.